LANDSCAPE AND THE SILENCE OF COLONIALISM NARRATIVE IN THE FIRST SUNDANESE NOVEL (1914) - Asep Yusup Hudayat; Lina Meilinawati; Teddi Muhtadin (Himpunan Sarjana-Kesusastraan Indonesia (HISKI), 2020)
The landscape (nature and domestic space) in the first Sundanese novel (1914) Baruang ka nu Ngarora” Poison for the Youth”, which was published during the colonial period of the Dutch East Indies, can be interpreted as ambiguous, which has the potential to show a palimpsest. The reasons are (1) the landscape (especially nature) in the novel has an atmosphere of silence, (2) the atmosphere cannot be interpreted as peaceful, but how the problems surrounding the practice of colonialism are likely to be hidden, diverted, or even interpreted, and (3) the landscape has the potential as a layered text based on memory traces inherent in narratives about the changing natural landscapes and domestic space. Thus, this study aims to uncover the potential of landscapes as areas of hiding, diversifying, and suppressing the narratives of colonialism. The approach used for this purpose is postcolonial. From a postcolonial perspective, Loomba (2003: 92-93) states that literature is also an important means of taking, reversing, or opposing the dominant colonial means and ideologies. This study also uses the palimpsest concept to show the overlapping phenomenon of pre-colonial and colonial narratives in the natural landscape and domestic space, which indicates the hidden narrative of colonialism behind this background. The result of this research is the silence of the narrative of colonialism in the background of natural landscapes and domestic space which is constructed as hiding and transferring of colonialism narratives.